High-order-harmonic generation using gas-phase H2O molecules - Zhao, Song-Feng; Jin, Cheng; Lucchese, R. R.; Le, Anh-Thu; Lin, C. D. (My University, 2011)
We investigate high-order-harmonic generation of isotropically distributed gas-phase H2O molecules exposed to an intense laser field. The induced dipole of each individual molecule by the laser field is first calculated using the recently developed quantitative rescattering theory. In a thin medium, harmonic spectra generated coherently from all the molecules are then calculated by solving Maxwell’s equation of propagation. By using accurate transition dipoles of H2O, we show that the harmonics in the lower plateau region are quite different from models that employ the simpler strong-field approximation. We also examine the magnitude and phase of the harmonics and their dependence on laser focusing conditions.